Pemberdayaan Ibu-Ibu PKK Melalui Pelatihan Pemanfaatan Buah Mengkudu Menjadi Dodol di Kecamatan Sukajadi Pekanbaru - Salmiah Salmiah; Indah Wati; Yulia Novita; Ristiliana Ristiliana (XXXXX, 2023)
This community service activity aims to empower PKK mothers through training on using noni fruit to make dodol in Sukajadi District, Pekanbaru. The implementation method in this service is carried out through 3 stages, namely the training preparation stage, activity implementation, and the final stage. The results of community service activities at the beginning of the activity said that the majority did not know how to make dodol from noni. In theory, I hope this dedication can improve community businesses or the family economy. The advantage of the output of this activity is that raw materials are easy to find, namely noni fruit and quality can be guaranteed by selecting good basic ingredients. The weakness of this output is that the processing process is quite complicated so that it takes a long time to make noni dodol.